Analysis of The Brazilian and World competitive Calendar of Beach Volleyball (1989-2019) - Leopoldo Sindice da Silva; Giuliano Batista Sucupira; Joanildo Costa Junior; Leandro Garrot Rodrigues; Abdallah Achour Junior (Universidade Salgado de Oliveira, 2020)
Sports management has shown its contributions to the success of a sport, in particular through the creation of a competition calendar. Due to this, the competitive calendar is fundamental for the development of the athlete, since it influences from the planning of training, to the regulation of the periodicity of tournaments. Thorugh understanding this importance and identifying a gap in this knowledge in beach volleyball, it is necessary to assess the changes that have occurred in the sporting calendar after decades of competitions. Thus, this study aimed to analyze all editions of the main competitive calendar of Brazilian and world beach volleyball. The research is characterized as descriptive through documentary analysis, from online searches on documents published on the websites of the Brazilian Volleyball Confederation and the International Volleyball Federation. The results showed a difference in the number of tournaments of the Brazilian tour, comparing the 1994 season (n = 19) with the last edition in 2018/2019 (n = 7), indicating a reduction of 63.15%. The world calendar has grown gradually through constant changes and new operational strategies. International management expanded the competitive calendar around the world, reaching its peak in 2018 ARTIGO ORIGINAL Silva et al 2020, Vol. 10, e10015 with 46 women's tournaments in a single season, showing a growth of 2,200% when compared to the first edition in 1993 (n = 2). These changes induce greater competitive opportunities for athletes, especially foreigners, and growth for the sport. However, the reduction of tournaments in the Brazilian calendar has a direct negative impact on national athletes and possibly on the future development of the sport in the country. In order to avoid this, it is suggested to develop a new competition format, as well as the opening for new sponsors, aiming a broader calendar with better competitive and financial conditions for the teams